Bonaventure: education for beauty in the knowledge of the world and of God - doi: 10.4025/actascieduc.v36i1.22268 - Gerald Cresta (Universidade Estadual de Maringá, 2014)
In the Middle Ages, the increasing autonomy on the nature of Beauty may be defined by three aspects that underscore the speculative approach on the concept: first, the Neoplatonic root in strict relationship with the Good (kalon); second, the Augustinian approach with its relationship between species and order, the factors that shine in created Beauty from the original divine source; third, the interpretation that predominated within Scholasticism and which gave to Beauty its transcendental beauty and established an intellectual distinction between the pulchrum and the bonum. Current research analyzes St Bonaventure´s position on the three perspectives and foregrounds the elaboration of the concept as from 'light' as a substantial form which traces a transcendental pedagogical scheme in which concepts and light bring accession modes to the knowledge of the world and its divine causal origin.